(untitled) (Papeles, 2014)
This paper presents the theoretical review and partial results of a qualitative research relevant to a thesis, comparing the pedagogical characteristics and their assessment of students learning implemented in eight Educational Institutions in Bogotá (EI), from the perspective of school administrators and teachers. It is a case study; the EI are differentiated by their performance (minimum and insufficient vs. satisfactory and advanced) on tests Saber 3 and 5. The methodology contemplated content analysis procedures such as coding, open and descriptive categorization of information collected in interviews and focus groups subsequently systematized with support from Atlas TI software. The results suggest tangential differences between pedagogical features such as learning explored the theoretical principles that guide teaching and learning, assessment and design of their distinction between evaluations is done in the classroom versus the ideal considered by the participants. The characteristics of the learning could not explain the results in evaluations Saber 3 and 5.